Fulminant Acute Ascending Hemorrhagic Myelitis Treated with Eculizumab - Hsam, Nang Boe Ohnmar; Angstwurm, Klemens; Peters, Sebastian; Fuchs, Kornelius; Schuierer, Gerhard; Bogdahn, Ulrich; Weissert, Robert (Frontiers in Neurology, 2017)
We describe an 18-year-old patient who developed back pain, rapidly ascending sensomotory deficits, bladder dysfunction, Lhermitte’s sign, absent abdominal reflexes of all three levels, brisk tendon reflexes, and positive Babinski’s sign. Magnetic resonance imaging of the spinal cord showed a long segment of cervical and thoracic intramedullary signal hyperintensity suggesting a longitudinally extensive transverse myelitis possibly within the course of a fast progressing ascending immune-mediated hemorrhagic myelopathy. Throughout his illness, the patient deteriorated with tetraplegia, cardiac arrest, and respiratory failure although he received, after exclusion of infective causes, therapy with steroids, immunoglobulins, plasmapheresis, and cyclophosphamide. Interestingly, treatment with the C5-inhibitor eculizumab to prevent complement-mediated spinal cord injury achieved an arrest of clinical deterioration. We propose eculizumab as treatment in fast progressive and potentially fatal immune-mediated spinal cord injury. Furthermore, this case raises awareness for the process of clinical decision-making in severe myelopathies.